2009
DOI: 10.2166/wqrj.2009.027
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Modelling of a Highway Wet Detention Pond Designed for Cold Climate

Abstract: A wet detention pond in Norway has been monitored for 12 months. The pond receives runoff from a highway with a traffic load of 42,000 average daily traffic. Hydraulic conditions in terms of inflow, outflow, and pond water level were recorded every minute. Water quality was monitored by volume proportional inlet and outlet samples. During most of the year, excellent pollutant removal was achieved; however, during two snowmelt events the pollutant removal was poor or even negative. The two snowmelt events accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The reduced performance efficiency is attributed to the minimal treatment in the presence of ice-cover on the surface of the infiltration basin. Poor performance of stormwater detention ponds during winter compared to other seasons has been reported in other studies also (Semadeni-Davies, 2006;Vollertsen et al, 2009).…”
Section: Resultssupporting
confidence: 59%
“…The reduced performance efficiency is attributed to the minimal treatment in the presence of ice-cover on the surface of the infiltration basin. Poor performance of stormwater detention ponds during winter compared to other seasons has been reported in other studies also (Semadeni-Davies, 2006;Vollertsen et al, 2009).…”
Section: Resultssupporting
confidence: 59%
“…These are quite high concentrations compared to other studies; Tromp et al [47] found PAH levels in Dutch runoff from highways to be 2.4 µg•L −1 . Similarly, Vollertsen et al [25] found total PAH concentrations (flow weighted average over one full year of monitoring) in Norwegian runoff to be 1.8 µg•L −1 . Part of the explanation for the differences could be the regulation of PAH in tires sold on the European market from January 2010 (restriction number 50 in Annex XVII of REACH limits).…”
Section: Sedimentsmentioning
confidence: 83%